SPY TOYS UNDERCOVER - Powers, Mark; Wesson, Tim (London : Bloomsbury, 2018)
Toy Story meets James Bond in the third book in this incredible action-packed series! Can Dan the teddy bear who is too strong, Arabella the rag doll with the bad temper and Flax the tech genuis robot rabbit save the day once more? When the world's most famous chocolate factory disappears, it is up to the Spy Toys to find out the truth - and fast! If the chocolate runs out, there could be riots from children everywhere! The Spy Toys are sent undercover into a school where they need to disguise themselves as regular pupils. Could this be their toughest challenge yet? They'll need all their wits about them to defeat this baddie. And one thing is for sure: these kids don't play nice! Featuring hilarious illustrations from Tim Wesson throughout, this series is perfect for fans of Pamela Butchart and David Solomons' My Brother is a Superhero.
Keywords: Children's stories, English; English fiction